The 10/90 report on health research, 2001-2002 - Global Forum for Health Research (Geneva, Switzerland :Global Forum for Health Research, 2002)
This 10/90 Report on Health Research 1999 presents the results of the 2nd Annual Forum held in Geneva on June 25-26, 1998. Chapter 1 provides an overview of the global forum for research through a detailed discussion on the future critical problems, the objectives of the Global Forum for Health Research and selection of five strategies in response to the problem. Chapter 2 presents a summary on the efforts made in research priority setting, particularly that of the Ad Hoc Committee on Health Research. Chapter 3 focuses on the three instruments used to improve the priority setting process, which includes analysis of the burden of the disease, monitoring resource flows, and cost-effective analysis of investments in health research. Chapter 4 confirms the association between poverty and ill health by reviewing Global Burden of Disease Study. Chapter 5 reviews the achievements made over the past year in Initiatives in Health Research directly supported by the Global Forum and Initiatives that received funding from the World Bank through Global Forum. Chapter 6 presents a summary on the lessons learned from the programs launched by different institutions over the past decades and outlines the characteristics of effective health researchers. Chapter 7 highlights the challenges in fund allocation for research and suggests the implementation of effective communication strategies to address these barriers. Finally, chapter 8 proposes the application of the five-step process developed by Ad Hoc Committee to address the health status of the community.
Includes bibliographical references.
Keywords: Health Research; Health Services; Poverty